A rational pharmacovigilance safety appraisal of topical pefloxacin 0.3% ophthalmological drops in bacterial conjunctivitis, in global multi-centre tertiary care hospitals - Hazra, Moumita (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Pefloxacin is a newer broad-spectrum bactericidal fluoroquinolone antibiotic, with superior antibacterial activity in vivo against pathogenic ocular gram-negative and anaerobic microorganisms and better pharmacokinetic properties. The objective of this clinical research study was the rational pharmacovigilance safety appraisal of topical pefloxacin 0.3% ophthalmological drops in bacterial conjunctivitis, in global multi-centre tertiary care hospitals. Methods: The 43 bacterial conjunctivitis patients were prescribed topical pefloxacin 0.3% ophthalmological drops, 2 drops in each eye after every 3 hours for 2 days, and 2 drops in each eye after every 6 hours for next 5 days. The pharmacovigilance safety appraisal was performed by monitoring the occurrence of adverse drug reactions, like, transient ocular burning or discomfort, ocular irritation, redness, stinging, pruritis, photophobia, ocular watering and dryness, and recording in Adverse Event Case Report Forms, on days 0, 3, 5, 7, 10, 15, 30, and on further follow-ups. Results: In this study, the safety assessment showed that only 1 patient had ocular discomfort in the eye. The occurrence of adverse effects was statistically non-significant. Thus, 0.3% pefloxacin ophthalmological drops treatment was safe and tolerable, among all 43 patients. Conclusions: Therefore, pefloxacin is a safe ocular antibiotic for treating bacterial conjunctivitis, with adequate drug tolerability exhibited by the patients.